2014
DOI: 10.1007/s11248-014-9844-6
|View full text |Cite
|
Sign up to set email alerts
|

A 90-day subchronic feeding study of genetically modified rice expressing Cry1Ab protein in Sprague–Dawley rats

Abstract: Bacillus thuringiensis (Bt) transgenic rice line (mfb-MH86) expressing a synthetic cry1Ab gene can be protected against feeding damage from Lepidopteran insects, including Sesamia inferens, Chilo suppressalis, Tryporyza incertulas and Cnaphalocrocis medinalis. Rice flour from mfb-MH86 and its near-isogenic control MH86 was separately formulated into rodent diets at concentrations of 17.5, 35 and 70 % (w/w) for a 90-day feeding test with rats, and all of the diets were nutritionally balanced. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
(56 reference statements)
2
12
0
1
Order By: Relevance
“…Although the reports do not indicate direct risks to human and animal health, when the details of all the reports are considered, certain effects were observed, such as statistically significant differences in clinical performance of SD rats in response to consumption of high amylose and resistant GM-rice (Zhou et al 2011). Song et al (2015) concluded that biochemical and hematological blood parameters were comparable when SD rats were fed with Bt transgenic rice (expressing cry1Ab). Broiler chickens fed with GM soybean (expressing an imidazolinone tolerance gene) had lower body weight in comparison to the controls.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although the reports do not indicate direct risks to human and animal health, when the details of all the reports are considered, certain effects were observed, such as statistically significant differences in clinical performance of SD rats in response to consumption of high amylose and resistant GM-rice (Zhou et al 2011). Song et al (2015) concluded that biochemical and hematological blood parameters were comparable when SD rats were fed with Bt transgenic rice (expressing cry1Ab). Broiler chickens fed with GM soybean (expressing an imidazolinone tolerance gene) had lower body weight in comparison to the controls.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The 90-day feeding study in rats has a unique advantage in the evaluation of GE food safety. Rats have been widely used for safety assessment of GE food, particularly for food from GE crops [2123]. Rats also have been used as a model for safety evaluation of meat derived from GE animals.…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios similares en ratas y pollos alimentados con arroz transgénico informan sobre alteraciones clínicas en parámetros hematológicos y en el peso de los animales (Zhou et al 2011;Song et al 2015).…”
Section: Resultados Y Discusiónunclassified